Experimentally verified finite element modeling and analysis of a conformable piezoelectric sensor. (25th June 2021) - Amiri, Nikta; Tasnim, Farita; Tavakkoli Anbarani, Mostafa; Dagdeviren, Canan; Karami, M Amin
Abstract: This paper presents development of a three dimensional finite element model for simulations of a conformable piezoelectric sensor utilizing COMSOL Multiphysics. The sensor has a multi-layer structure composed of four circular piezoelectric elements arranged in an array structure laminated on a soft substrate and is capable of providing a strain mapping of soft tissue surfaces for spatiotemporal biokinematic assessment of the facial skin. Here, we provide the finite element method (FEM) for the sensor to predict its electromechanical behavior. This paper studies the effect of the design parameters such as dimensions of the piezoelectric sensor and the substrate on voltage sensitivity and sensor compliance. The FEM model is established to understand the underlying physics and guide the mechanical characterization of the system. The developed model is experimentally verified through two series of tests. The first set of tests involve comprehensive in vitro mechanical testing to provide accurate measurements of strain during compression, stretching, and bending. The second set of tests present in vivo experiments on healthy and amyotrophic lateral sclerosis subjects. The experimentally verified FEM model provides a detailed insight into analyzing the response of the sensor which establishes new design rules for next generations of conformable piezoelectric sensors.